Pembentukan Struktur Negosiasi Kota Surakarta: Kritik Nalar ‘Best Practices’ dalam Penyelenggaraan Pemerintahan - Hendra Try Ardianto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2011)
This paper attempts to describe two fundamental ideas about best practices. Firstly, criticism of the notion of